WORK OF MEDICAL STAFF IN PHYSIOTHERAPY ROOMS CONDITIONS - Sadirova M. K.; Umedova M. E. (The Conference Hub, 2025)
At the current stage of development of society, in the conditions of scientific and technological progress, the flow of incoming information is constantly increasing. The assimilation of this information and the effective development of new ideas require a significant activation of human mental activity. The need for highly qualified specialists is growing.